Oral health status of adults in Southern Vietnam - a cross-sectional epidemiological study - Truong Nhan B; Bronkhorst Ewald M; Witter Dick J; Nguyen Thoa C; Creugers Nico HJ (BMC, 2010)
Abstract Background Before strategies or protocols for oral health care can be advised at population level, epidemiological information on tooth decay patterns and its effects on oral function are indispensable. The aim of this study was to investigate influences of socio-demographic variables on the prevalence of decayed, missing, filled (DMF) and sound teeth (St) and to determine the relative risk of teeth in different dental regions for D, M, and F, of adults living in urban and rural areas in Southern Vietnam. Methods Cross-sectional DMF and St data of 2965 dentate subjects aged 20 to 95 living in urban and rural areas in three provinces were collected by means of a self-administered questionnaire and an oral examination. The sample was stratified by age, gender, residence and province. Results The percentage of subjects having missing teeth was high for all ages while it was low for subjects with decayed and filled teeth. The mean number of missing teeth increased gradually by age from approximately 1 in each jaw at the age of 20 to 8 at the age of 80. The number of decayed teeth was relative low at all ages, being highest in molars at young ages. The mean number of filled teeth was extremely low at all ages in all dental regions. Every additional year of age gives a significantly lower chance for decay, a higher chance for missing, and a lower chance for filled teeth. Molars had a significantly higher risk for decay, missing and filled than premolars and anterior teeth. Females had significantly higher risk for decayed and filled teeth, and less chance for missing teeth than males. Urban subjects presented lower risk for decay, but approximately 4 times greater chance for having fillings than rural subjects. Low socio-economic status (SES) significantly increased the chance for missing anterior and molar teeth; subjects with high SES had more often fillings. Conclusions The majority of adults of Southern Vietnam presented a reduced dentition. The combination of low numbers of filled teeth and relative high numbers of decayed and missing teeth indicates that the main treatment for decay is extraction. Molars are more at risk for being decayed or missing than premolars and anterior teeth.